(3eG jYhd Ydjg aj GdeVGa h GdeVGa Edjg (B/ (3JCdja eMeO GdCejf GdeMHj ; JMbjb Ydj EHQGgje cQOj(B.s - (3eMHj, eMeO Cejf Hf aVd Gddg, (B1651-1699.s; (3cQOj, Ydj EHQGgje(B.s ((3CHh XHj (B: s (3gjFI CHh XHj ddKbGaI h GdJQGK, OGQ GdcJH GdhWfjI,s, 2011)
(3L(B. 1. (3C(B-(3H (B-- (3L(B. 2. (3J(B-(3U (B-- (3L(B. 3. (3V(B-(3j (B-- (3L(B. 4. (3GdagGQS(B.s
Keywords: (3GddZI GdYQHjI(B--(3eYGLe(B.s